Induction Material Notes on the Functioning of Various Divisions 1996 - Planning Commission (Planning Commission, 1996)
The document presents an overview of the role, structure, and functioning of the Planning Commission of India, highlighting its central position in formulating and coordinating Five-Year and Annual Plans for national development. It explains the Commission’s core functions, including resource assessment, policy coordination, implementation monitoring, project appraisal, and public participation, particularly in the context of economic reforms and liberalization. The summary further outlines the specialized divisions within the Commission that address key sectors such as energy, environment, finance, health, rural development, industry, and international economic relations. Emphasis is placed on multi-level and decentralized planning, evaluation of development programs, and the integration of social, economic, and environmental objectives. Overall, the document underscores the Planning Commission’s comprehensive and adaptive approach to promoting inclusive, balanced, and sustainable development in India.
Government of India Planning Commission
Government of India Planning Commission
Keywords: Planning Commission; Five Year Plans; Resource Assessment; Project Appraisal; Sectoral Divisions; Rural Development; Financial Planning; Environmental Management; Programme Evaluation; Decentralized Planning